2019
DOI: 10.1016/j.healthplace.2019.05.019
|View full text |Cite
|
Sign up to set email alerts
|

The influence of alcohol outlet density and advertising on youth drinking in urban Tanzania

Abstract: Despite the detrimental effects of alcohol on adolescent health, high rates of alcohol use are reported among Tanzanian youth. We conducted systematic community mapping and participatory group activities with 177 adolescents in Dar es Salaam to explore how alcohol outlet density and advertising may contribute to adolescent drinking in urban Tanzania. Findings revealed a high density of alcohol-selling outlets and outdoor advertisements. The abundance of alcohol-related cues, including their close proximity to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 31 publications
0
30
1
Order By: Relevance
“…While the topic of alcohol marketing exposure and its assessment have gained some interest by researchers relatively recently [ 31 37 ], few studies have yet to systematically assess alcohol marketing exposure. While we chose the container-based approach which has been used previously, those studies were in very different contexts in both Tanzania [ 33 ] and South Africa [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the topic of alcohol marketing exposure and its assessment have gained some interest by researchers relatively recently [ 31 37 ], few studies have yet to systematically assess alcohol marketing exposure. While we chose the container-based approach which has been used previously, those studies were in very different contexts in both Tanzania [ 33 ] and South Africa [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 41 ]. However, in our review of the published literature, the container-based approach is the only method used so far in establishing alcohol marketing density in sub-Saharan Africa and that approach was recently implemented in Tanzania [ 33 ] and in South Africa [ 36 ]. The container-based approach is also a recommended strategy for monitoring alcohol marketing by NGOs [ 42 ].…”
mentioning
confidence: 99%
“…High alcohol outlet density has been associated with heavy drinking and risky sexual behaviour (Ibitoye et al, 2019;Letsela et al, 2019). In addition, a linear relationship between alcohol outlet density and alcohol consumption, and a range of alcohol-related harms has been established (Popova et al, 2009;Treno et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the physical environment, in particular, the location and concentration of alcohol outlets and the impact on youth drinking (Ibitoye et al, 2019;Letsela et al, 2019;Ransome et al, 2019) has received much attention. Much research in this area was limited to alcohol outlets only and not illicit drug use outlets and did not focus on proximity to young people's homes.…”
Section: Introductionmentioning
confidence: 99%
“…Although alcohol producers often argue that advertising does not influence drinking [34], empirical evidence suggests otherwise. For example, studies in Nigeria [64], Tanzania [65] and South Africa [66] have found that advertising is associated with drinking among young people. A recent South African study also revealed that exposure to alcohol advertising and promotions via SMS and point‐of‐purchase free offers facilitated heavy drinking [67].…”
Section: Key Findingsmentioning
confidence: 99%